Time-dependent assessment of aircraft cable current capacity for lightweight design - Ali Can Yılmaz; Ahmet Akbulut (Engineering Science and Technology, an International Journal)
This study proposes a time-dependent methodology for determining the current-carrying capacity of aircraft cables, addressing limitations in aviation standards such as AS50881. The aim is to enable more efficient cable selection by accounting for short-term, high-current scenarios — such as engine start-up or actuator engagement — that are typically neglected in existing standards. The proposed model incorporates environmental and operational parameters including ambient temperature, altitude, bundling conditions, and current duration. An empirical formula is developed and experimentally validated using a custom test setup replicating realistic aerospace conditions. Comparative analysis with other approaches demonstrates that the proposed method allows for accurate current rating while enabling significant reductions in cable size and weight. Experimental results indicate that current capacity predictions by AS50881 are conservative by approximately 12%, confirming opportunities for optimization. A case study on a two-pilot aircraft shows that adopting the proposed approach could reduce wiring weight by up to 20%, without compromising safety. This research provides a practical framework for incorporating time-dependent behavior into cable sizing, offering substantial benefits in terms of efficiency, sustainability, and compliance in modern aircraft wiring systems.